2019
DOI: 10.3892/ol.2019.10854
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RAD54 homolog B as a promising therapeutic target for breast cancer

Abstract: Breast cancer is a recognized threat to the health of women globally. Due to the lack of the knowledge about the molecular pathogenesis of breast cancer, therapeutic strategies remain inadequate, especially for aggressive breast cancer. In the present study, sequential bioinformatics analysis was performed using data from the GSE20711 dataset, and the results demonstrated that three genes may impact the survival of patients with breast cancer. One of these genes, RAD54 homolog B (RAD54B), may be a potential pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…However, its importance in anticancer therapy needs further investigations. In fact, alterations of RAD54B have been detected in several cancers, including lung adenocarcinoma, breast cancer, and hepatoma ( 44 , 45 , 46 , 47 ). RAD54B silencing often leads to reduced cell proliferation and enhanced apoptosis ( 44 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, its importance in anticancer therapy needs further investigations. In fact, alterations of RAD54B have been detected in several cancers, including lung adenocarcinoma, breast cancer, and hepatoma ( 44 , 45 , 46 , 47 ). RAD54B silencing often leads to reduced cell proliferation and enhanced apoptosis ( 44 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…JaponiconeA (JA) is a natural product isolated from Inula japonica Thunb 16 . A previous study showed that JA inhibited breast cancer cell proliferation by inhibiting the expression of RAD54B 17 . Moreover, JA inhibited the growth of non-small cell lung cancer cells via mitochondrial-mediated pathways 18 .…”
Section: Introductionmentioning
confidence: 98%
“…JaponiconeA (JA) is a natural product isolated from Inula japonica Thunb (16). Previous study has demonstrated that JA inhibited breast cancer cell proliferation by inhibiting the expression of RAD54B (17).And JA could inhibit the growth of non-small cell lung cancer cells via mitochondria-mediated pathways (18). In addition, JA was also effective in Burkitt lymphoma (19)Here, we found that JA showed potent anti-tumor effect in MM both in vitro and in vivo but spared the normal cells.…”
Section: Introductionmentioning
confidence: 99%